A ressignificação do brand publishing : uma análise da influenciadora virtual Lu do Magalu - Lima, Raniella Barbosa de (2023)
The dissertation is characterized as theoretical-practical with the object of study identifying and describing the new meanings of brand publishing around the Magalu brand on digital social networks with the virtual influencer Lu, based on the relational construction between the brand and its users- consumer-citizens. The theoretical-methodological framework addresses issues related to digital influence, organizational reputation, digital influencers, media disintermediation, brands as publishers and digital influencers, relationship management and public relations activity in the digital environment. The basic methodology is bibliographical research, as well as a single case study associated with qualitative empirical collection of a Netnographic type with the monitoring of profiles on digital social networks of the Magalu brand. And finally, the procedures for analyzing the results were carried out through critical discourse analysis (CDA) according to the precepts of Norman Fairclough. The results indicate new meanings for brand publishing: brands acting as digital influencers through virtual avatars, where content, data management and operability are valued, especially due to the emergence of artificial intelligence. From the perspective of organizational communication, the new meanings of brand publishing go beyond the classic understanding of the organizational communication diagram defended by Margarida Kunsch (2003): internal, marketing and institutional. Brand publishing changes this organizational communication mix through proprietary media, which becomes the center of an integrated organizational communication mix.